Skin intrinsic fluorescence scores are a predictor of all-cause mortality risk in type 1 diabetes: The Epidemiology of Diabetes Complications study - Tomaszewski, Erin L. (J Diabetes Complications, 2020)
AIMS: We assessed the association of skin intrinsic fluorescence (SIF) scores, as a measure of advanced glycation end-products (AGE), with all-cause mortality in type 1 diabetes (T1D). METHODS: This is an observational retrospective study of a convenience sample from the Epidemiology of Diabetes Complications (EDC) study. AGEs were measured with a SIF score between 2007 and 2014; vital status was assessed in 2020. RESULTS: Among 245 participants, mean age was 48.6 ± 7.4 years, median diabetes duration was 39.5 years (IQR: 34.2, 44.9), and 53.5% were female. Compared to survivors, the deceased (n = 20) were older, with higher SIF scores, longer diabetes duration, lower body mass index (BMI), and an adverse risk factor profile (all p≤0.05). Univariate Cox regression showed a marginal association between SIF score and mortality (HR: 1.1, 95% CI 0.9–1.2, p = 0.06), which persisted after adjustment for multiple daily insulin shots/pump (MDI) use (HR: 1.1, 95% CI 1.0–1.2, p = 0.04). This association was attenuated after adjustment for T1D duration, A(1c) months, or estimated glomerular filtration rate (eGFR). CONCLUSIONS: In individuals with long duration T1D, SIF scores adjusted for MDI predicted all-cause mortality, although this association was attenuated after adjustments. Given the nature of sampling and small number of events, our findings require replication.